Information Sources Utilization and Adoption Behaviour of Pineapple Growers in Nagaland (Indian Journal of Extension Education, 2024)
Pineapple being one of the important horticultural crops of Nagaland, adoption of sustainable cultivation practices is crucial with changing climatic conditions. The study was conducted in Nagaland during 2018-2022 to evaluate the factors influencing the use of information sources and technology adoption for sustainable pineapple cultivation. Altogether 275 respondents were selected from 13 villages representing three leading pineapple growing districts of Nagaland using proportionate random sampling. The study revealed that informal sources of information were most preferred by the respondents. Selection of improved varieties, planting materials, weed management, ratooning, storage, and post-harvest management practices were fully adopted by the respondents. Variables viz., size of land under pineapple cultivation, annual income, income from pineapple cultivation, training exposure, experience, social participation, attitude, economic motivation, and knowledge had significant relationships with the information sources utilization and technology adoption. The coefficient of determination (R2) was 0.582 and 0.581 for explaining the utilization of information sources and adoption respectively. It is recommended that strengthening extension-farmer linkages and improving digital literacy may help enhance the efficacy of the information sources as well as improve technology adoption by pineapple growers.